1995
DOI: 10.1111/j.1365-3083.1995.tb03700.x
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Membrane Cofactor Protein of Complement (CD46) in Human Leukaemia Cell Lines: Implication of an Alternatively Spliced Form Containing the STA Domain in CD46 Up‐Regulation

Abstract: Human membrane cofactor protein (MCP, CD46) is a receptor for the measles virus and serves as a complement regulator which protects host cells from autologous complement attack. MCP is highly polymorphic due to a variety of mRNA splice products. The levels of MCP expression on T and myeloid cell lines are usually two-eightfold higher than those on their normal counterparts, whereas Burkitt's lymphoma B cell lines express less MCP than B cell lineages carrying no EB virus. The molecule has a Ser/Thr-rich (ST) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…The wide distribution of HHV-6 in vitro and in vivo is consistent with the ubiquitous nature of its receptor, CD46 [Santoro et al, 1999]. The expression of the CD46 receptor is also found on malignant cells and particularly on leukemia cells [Hara et al, 1995]. However, CD46 is not sufficient by itself to enable HHV-6 fusion, thus the virus might require an additional factor, possibly a viral co-receptor, to make cells permissive to infection.…”
Section: Introductionmentioning
confidence: 57%
“…The wide distribution of HHV-6 in vitro and in vivo is consistent with the ubiquitous nature of its receptor, CD46 [Santoro et al, 1999]. The expression of the CD46 receptor is also found on malignant cells and particularly on leukemia cells [Hara et al, 1995]. However, CD46 is not sufficient by itself to enable HHV-6 fusion, thus the virus might require an additional factor, possibly a viral co-receptor, to make cells permissive to infection.…”
Section: Introductionmentioning
confidence: 57%
“…The cellular receptor of HHV-6 is CD46, expressed on the surface of normal and malignant cells as well as on leukemic cells [4]. HHV-6 oncogenic potential was demonstrated in vitro in NIH3T3 cells [5], and ORF-1, also referred to as DR7, was identified as an oncogene.…”
Section: Introductionmentioning
confidence: 99%
“…The expression ratio of the four main isoforms is inherited in an autosomal codominant fashion, with three phenotypes in the population: the majority (65%) expresses predominantly the highly O -glycosylated BC1/2 forms, 6% express predominantly the less glycosylated C1/2 forms, and 29% of the population express both forms in roughly equal amounts (Liszewski et al 1991;Wilton et al 1992;Seya et al 1999). The carboxyl terminus of CD46 is also differentially spliced, giving rise to two distinct cytoplasmic tails, designated CYT-1 (16 amino acids) and CYT-2 (23 amino acids) 3 Measles Virus and CD46 35 EBV-transformed lymphocytes and leukemic cell lines (ABC1/2) and in the placenta (B1/2) (Hara et al 1995;Matsumoto et al 1992;Russell et al 1992;Purcell et al 1991;Johnstone et al 1993), has not been identified. Soluble forms of CD46, possibly shed from the cell surface via metalloproteinases (Hakulinen and Keski-Oja 2006), are present in low concentrations in plasma, seminal fluid, and tears (Hara et al 1992;Simpson and Holmes 1994).…”
Section: Structure and Isoformsmentioning
confidence: 99%